Curitiba: The First Creative Sustainable City in Brazil - Feitosa, Maria José G (MAJ - Malaysia Architectural Journal, 2025)
The drive for sustainability in Brazil began in the city of Curitiba, State of Parana, through 3 successive administrations of Mayor Jaime Lerner between 1971 and 1992. During this period, collaboration between the public and private authorities and the inclusion of all social classes and age groups was formed. There was a huge population growth in this city: in 1971 according to the IBGE (Brazilian Institute of Geography and Statistics) it was 356.830 inhabitants, reaching in 2022 about 1.773.733 inhabitants. The relationship between population density and sustainability advances will be analyzed. The thinking about the environment began with the research of an existing inventory of fauna and flora, aiming at the formation of more green areas for Curitiba and being under the responsibility of the Department of Research and Squares.Curitiba exceeded the who recommendation, regarding green areas, which foresees 12m² and reached 40m²/inhabitants. The Master Plan of Curitiba, as new needs arise, is systematically readjusted and corrected. Sustainability covered the various Departments of te City Hall, aiming at the preservation of green areas, fed by environmental actions, the reduction of polluting gas emissions, through the non-polluting bi-articulated electric bus, called “green transport”. The clear goals were achieved through the development of clean energy profects, food security (vegetable gardens and Urban Farm), recycled material in exchange for plant products, solar energy, composting program, culminating in the reurbanization of a suburban neighborhood, where all green renovation is being applied. These programs are evaluated and improved every six months, talking into account population growth and seeking new advances